Clinical Efficacy of Topical Antioxidants for Skin Photoaging: A Two-Decade Systematic Review - Brilian Veda Kartika Putri; Gisela Meydilin Sanjaya; Hany Anneke; Nayla Majeda Alfarafisa; Astrid Feinisa Khairani (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Skin photoaging is driven predominantly by ultraviolet-induced oxidative stress, resulting in wrinkles, pigmentation, loss of elasticity, and skin barrier dysfunction. Topical antioxidants have been proposed as both preventive and corrective interventions; however, the clinical evidence remains fragmented. Objective: This systematic review aimed to evaluate the efficacy and safety of topical antioxidants for the prevention and treatment of skin photoaging. Methods: A systematic search of PubMed, Scopus, ScienceDirect, and the Cochrane Library was conducted through August 2025 following the PRISMA 2020 guidelines. Randomized controlled trials, controlled clinical trials, and prospective interventional studies involving adults with photoaged skin were included. The risk of bias was assessed using RoB 2.0 and ROBINS-I. Of the 1,740 identified records, 23 studies met the eligibility criteria. Results: Vitamin C, vitamin E, ferulic acid, niacinamide, bakuchiol, and plant-derived antioxidants significantly improved wrinkles, pigmentation, skin hydration, and skin elasticity. Combination formulations, particularly vitamin C–vitamin E–ferulic acid serums, demonstrated enhanced efficacy, whereas bakuchiol achieved wrinkle reduction comparable to that of retinol with better tolerability. Topical antioxidants also showed benefits in the management of melasma, postprocedural recovery, and actinic keratosis, with adverse events generally limited to mild, transient irritation. However, heterogeneity in study design, antioxidant formulations, and follow-up duration limited direct comparisons across studies. Conclusion: Topical antioxidants are effective and well-tolerated interventions for skin photoaging, supporting their integration into long-term dermatologic practice. Further large-scale, standardized clinical trials with longer follow-up periods are required to strengthen the evidence.